Modeling stress distribution analysis on plate with hole using new mesh method - Mulyadi, Mulyadi (Rekayasa Material, Manufaktur dan Energi, 2025)
Stress concentration around circular holes in plates is a critical challenge in structural analysis. Traditional FEM requires fine meshes near discontinuities for accurate predictions, increasing computational cost. This study introduces a novel, adaptive, geometry-aware mesh method that refines only near the hole while keeping the rest of the mesh coarser. Simulations under uniaxial tension are compared to conventional mesh strategies and analytical solutions. Performance is evaluated by accuracy, convergence, and computational efficiency.